Pengelolaan Ikan Hias Dan Konsumsi Kelompok Al-Ayyubi di Pancoran Jakarta Selatan - Iskandar, Donant Alananto; Dara, Siti Ruhana; Sumbogo, Ignatius Ario (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
This Community Service Program has been implemented in April 2024 at the Al-Ayyubi Ornamental Fish Cultivation and Consumption Group Jl. Pancoran Barat IXG, RT08/RW03, Kelurahan Pancoran, Kecamatan Pancoran, South Jakarta 12780. The problem faced by the Al-Ayyubi Ornamental Fish Cultivation and Consumption Group is that the management of ornamental fish cultivation and consumption ponds has not been maximized. The aim to be achieved is to motivate the group in managing ornamental fish cultivation and consumption ponds. The method used is a social approach method in the form of counseling and training. This program begins by educating the public with knowledge about the use of fish farming ponds through counseling and assistance, then continues with practicing in the field or in ponds near the RT office. So that the community can practice and develop fish farming management patterns in the group. The achievements that will be obtained after training and counseling are carried out, the group can manage, carry out fish cultivation properly, correctly and can make optimal use of fish cultivation pond land, therefore it can increase the income of community empowerment groups.